O imaginário das lendas e mitos amazônicos na escola: a prática do letramento por meio da criação de histórias em quadrinhos - CASTRO, Silvia Margareth dos Santos (2019)
This work aims to present the construction of HQ comics with Amazon legends and myths, especially from the municipality of Muaná-Pa, as an indispensable tool in the literacy process of the students of the 6th year of elementary school. For this a school was chosen located in the riverside area of the mentioned municipality, which works with elementary school. The work is developed through bibliographic research, based on some authors of the area, application of questionnaires to students and teacher and an intervention plan carried out in the class. The use of HQ allows the student to autonomously understand and interpret the texts he / she has read and leads the teacher to realize the relevance of developing independent, critical and reflective readers. Therefore, teachers are offered concrete means to carry out coherent activities that favor the insertion of the student in the scope of reading and writing via literacy within the Amazon context.